Denture Stomatitis with Diabetes Mellitus and Anemia: A Case Report - Rambe, Sarinah; Rifki, Ayudia; Ulfah, Khairiyah; Husna, Nurul; As Syifa, Salwa (Indonesian Dental Association, 2025)
Introduction: Denture stomatitis (DS) is a common problem among denture wearers. It usually appears as redness or inflammation of the oral mucosa that encounters the denture base. The causes are often not limited to one factor. Poor denture hygiene, wearing dentures continuously, and ill-fitting dentures are common triggers. However, systemic conditions such as diabetes mellitus can also play a major role by reducing the body’s ability to fight infection. Case Report: A 54-year-old woman presented to the Dental Hospital at Universitas Syiah Kuala with complaints of redness on the hard palate. She mentioned that her denture had become loose and often fell out when she talked or chewed food. Intraoral examination revealed diffuse erythematous, measuring >2 cm, red in color, number 2 (bilateral), irregular edges, located on the hard palate. Atrophic lesions, flat, measuring ±3x5cm, red in color, multiple, with diffuse borders and irregular edges, located on the dorsal surface of the tongue. Blood examination revealed elevated blood glucose and HbA1c levels, along with low hemoglobin, hematocrit, Mean Corpuscular Volume (MCV), and Mean Corpuscular Hemoglobin (MCH) values. Based on the patient’s history, clinical features, and laboratory results, the case was diagnosed as denture stomatitis type II (Newton’s classification) associated with diabetes mellitus and mild anemia. The patient was treated with Nystatin oral suspension and Chlorhexidine Gluconate 0.2%, blood glucose control and improved nutrition were emphasized to support the healing process and enhance systemic health. In addition, the patient was advised to adjust the denture. Conclusion: Management of this condition must be comprehensive, starting with proper diagnosis of the causative and risk factors, then directing treatment to the most significant factors specific to the patient.